2018
DOI: 10.1103/physrevb.97.155409
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the overlap between Majorana fermions by orbital magnetic effects in semiconducting-superconducting nanowires

Abstract: We study both analytically and numerically the role of orbital effects caused by a magnetic field applied along the axis of a semiconducting Rashba nanowire in the topological regime hosting Majorana fermions. We demonstrate that the orbital effects can be effectively taken into account in a one-dimensional model by shifting the chemical potential, and, thus modifying the topological criterion. We focus on the energy splitting between two Majorana fermions in a finite nanowire and find a striking interplay bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…The Majorana overlap, which is a measurement of the degree of non-locality of the two Majorana wave functions, mostly depends on the length of the nanowire (and to a lesser extent on other parameters, such as the induced superconductor gap and the Rashba coupling), but it is not necessarily correlated to the Majorana energy splitting. Different mechanisms can reduce this splitting, such as interactions with the environment as studied here, smooth potential or gap profiles [21,2628 30], or orbital magnetic effects [31], and still leave the Majorana overlap unaffected. The behavior of the Majorana wave functions in this case is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Majorana overlap, which is a measurement of the degree of non-locality of the two Majorana wave functions, mostly depends on the length of the nanowire (and to a lesser extent on other parameters, such as the induced superconductor gap and the Rashba coupling), but it is not necessarily correlated to the Majorana energy splitting. Different mechanisms can reduce this splitting, such as interactions with the environment as studied here, smooth potential or gap profiles [21,2628 30], or orbital magnetic effects [31], and still leave the Majorana overlap unaffected. The behavior of the Majorana wave functions in this case is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conspicuously, in most of the available experimental data the emergence of a robust zero-bias conductance peak is observed above some critical Zeeman field without the expected oscillatory pattern [12,19,2425]. Several mechanisms have been proposed to account for the reduction or lack of oscillations, such as smooth confinement [21,2628], strong spin–orbit coupling [29], position-dependent pairing [30], orbital magnetic effects [31], Coulomb repulsion among the carriers in the nanowire [22], or the presence of the normal drain lead connected to the hybrid wire [32]. …”
Section: Introductionmentioning
confidence: 99%
“…However, these behaviors are sharply opposite to the theories for the Majorana bound states [29], which predict an enhanced oscillation amplitude and period. Several theoretical studies [37][38][39] have tried to address this discrepancy, but are partially successful, e.g., assumed multiple subbands and temperatures higher than those in the experiments [37] or found that the oscillation period decreases with increasing magnetic field [38,39]. This discrepancy has raised the concerns on the conclusive identification of Majorana bound states, and has even endangered the scheme of Majorana qubits based on the nanowires [40,41].…”
mentioning
confidence: 99%
“…µ(x) and α(x) denote the positiondependent chemical potential and spin-orbit coupling, respectively. Quite different from the previous theories which assume a constant spin-orbit coupling [37][38][39], we model that spin-orbit coupling has a profile [see also the green curve in Fig. 1(a)]…”
mentioning
confidence: 99%
“…30-36. In this planar geometry, a perpendicular magnetic field has a paramount influence on the motion of quasiparticles in the plane; the scenario of the well studied quantum Hall effect. In our context of hybrid semiconductor-superconductor systems, the relevance of the magneto-orbital effect for the characterization of topological phases has been studied in different geometries; cylinders, [37,38] faceted wires [27,28] and 2D strips or ribbons [39][40][41]. In 2D strips it is generally assumed that a perpendicular field is detrimental for the Majorana modes and a parallel field is more often consid-ered where the magnetic effect is restricted to a Zeeman coupling with the quasiparticle spin.…”
Section: Introductionmentioning
confidence: 99%